CODESRIA Bulletin Online, No. 3, April 2025 - Selection Report for the ACADEMIC FREEDOM CONFERENCE 2025 Dar es Salaam, Tanzania 29 April to 02 May 2025 - Training, Grants and Fellowship Programme, (CODESRIA Bulletin, 2025)
Introduction Under the intense gaze of democracy-watchers, Africa has been ﬂagged repeatedly as a site of persistent abuse of academic freedom, and African countries, like many countries in the global South, have been highlighted for declining ratings on the Academic Freedom Index. In more recent times, however, the spectre of declining academic freedom has spread its shadow, and intellectual constraints are now an acknowledged problem in countries hitherto reputed to have resisted them. It is now recognised that there is a global decline in academic freedom. The guiding principle of CODESRIA’s Strategic Plan 2023-2027 is “to raise important questions about the environment in which intellectual work is conducted in Africa”. To meet this challenge, the Council decided to revive its academic freedom programme, which had been launched after the November 1990 Kampala Conference but had been stalled for a while by fund- ing challenges. Starting with a series of convenings organised in Tanzania and Mozambique, along with a brainstorming workshop in Dakar in November 2024, the Council has repositioned academic freedom as a ﬂagship programme. This is the context of the Council’s decision to convene a conference on Academic Freedom in Africa in 2025, with the review of the Kampala Declaration as the main entry point. The conference aims to situate academic and intellectual freedom within the broad societal context while exploring the trans- formative and developmental man- date of academics. The call for applicants to submit full papers to be considered for presentation at the conference, scheduled to take place from 29April to 2 May 2025, was disseminated in December 2024. The deadline for the call was extended from 15 January to 31 January 2025, owing to the high number of incoming applications, which was more than anticipated, and the indication by many prospective applicants that they were unable to complete their papers and submit their applications by the deadline. Purpose of the Report This report summarises the selection process for participation in the conference. The Council received 220 applications through the on- line application system. These applications came from 35 countries across four continents, including Europe, Asia and North and South America. A total of 52 applications, representing 23.6 per cent of the whole, were from female applicants, and 168 applications, rep- resenting 76.4 per cent, were from male applicants. Figures 1 and 2 illustrate the distribution of applications received by gender and language. Some 76 per cent of applications (169) were from English-language applicants, 22 per cent from French-language applicants (38) and 2 per cent from Portuguese- language applicants (3). The small number of applications in other languages reﬂects a historic imbalance in CODESRIA o^icial languages, but it must be noted also that the Council did not issue a call for applications in Portuguese, which explains the low level of applications in that language. Figure 1: (View PDF File) Figure 2: (View PDF File) In most calls for applications by CODESRIA, countries such as Cameroon, Nigeria, South Africa, Uganda, Kenya and Zimbabwe predominate. In this call, CODESRIA received 33, 32, 23, 20 and 16 applications for these countries, respectively. At the other end, countries such as Chad, Swaziland, Madagascar and Eritrea remain minimally represented; in this call, each had one applicant. North Africa contributed 10 applications, from Egypt, Morocco and Tunisia (3 each), and Algeria (1). Outside Africa, applications came from the USA (4), the UK (3), the United Arab Emirates (2), and one each from Brazil, Canada and Italy (Table 1). Table 1: (View PDF File) The regional pattern of application shows an imbalance with respect to North Africa. Whereas the Council received 53 applications from East Africa, 52 from West Africa, 41 from Central Africa and 52 from southern Africa, it received only 10 from North Africa. A closer look at the application data reveals disparities within regions, with some countries consistently dominating and others remaining underrepresented. In East Africa, Uganda (23) and Kenya (20) led in applicants, followed by Tanzania and Ethiopia (4 each), and then Rwanda and Eritrea, with one each. In West Africa, Nigeria (23) and Côte d’Ivoire (7) stand out. Figure 3: (View PDFFile) The Screening Process The Secretariat screened applications in 3 main stages to ensure that only complete and thematically relevant papers were advanced to the peer-review phase. The screening process began with identifying incomplete submissions. Applicants were required to submit full research papers (5,000–7,000 words), but 24 abstracts were mistakenly submit- ted instead. These applicants were given an extra week to complete their submissions; only 4 met the extended deadline. Next, a thematic review ensured that the papers aligned with the conference call. Irrelevant submissions were either recommended for consideration for publication in CODESRIA’s journals or for inclusion in research on Indigenous knowledge systems. Finally, sub- missions from invited reviewers were excluded to uphold the integrity of the double-blind peer-re- view process, preventing conﬂicts of interest. A total of 173 applications advanced to the double-blind review stage, and these maintained regional and country representation trends. Nigeria led with 28 appli- cants, followed by Cameroon (26), Kenya (18), South Africa (17), Uganda (16) and Zimbabwe (11). DRC and Côte d’Ivoire each had 6 applicants, while Ghana, Tanzania, and Senegal retained 4 papers each. Morocco and the USA had 3 applications apiece, with other countries contributing one or two submissions. The Review Process Each anonymised paper was as- signed to two reviewers via CODESRIA’s online platform. Over 3 weeks, 36 reviewers evaluated the submissions. In identifying the reviewers, the Secretariat considered language, expertise and geographical representation. Using a provided review guide and grading scale, the reviewers assessed relevance and quality, categorising papers as poor, average, good or excellent, and assigning scores from 0 to 10. Papers with a score below 3 were rejected. Papers be- tween 4 and 6 were treated as potentially good but required revision. Papers scored between 7 and 10 received a direct invitation for presentation at the conference. The Selection Process The Secretariat moderated the scores by the two reviewers assigned to each paper. An average score was generated for each of the papers, and all papers with an average score of 7 and above were automatically invited to the conference. Countries with more applications were placed to compete among themselves, emphasising the quality of applications, with those above 7 selected. A total of 35 applications, all with a score of 7 and above, were retained. These included 9 female applicants and 26 male applicants from 18 countries. Of all 173 applications re- viewed at the double-blind stage, 81 scored an average of 6 and above, which constituted a 47% acceptance rate based on the review guide provided. Applicants with a score of 6 and above were further moderated with an emphasis of meeting a speciﬁc diversity threshold, including gender, regional and country representation and thematic coverage. Since only 9 female applicants were retained in the ﬁrst round of selections of applicants, the second round of selection prioritised female applicants. Applicants from less-represented countries were also prioritised, while applicants with a speciﬁc thematic focus that the Secretariat needed at the conference were retained. Tanzania- based applicants within this range were also retained since the cost of supporting their participation to the conference would be minimal. Five applications were retained from the second phase of selection, making a total of 40 applicants. In the ﬁnal round of moderation of applicants with an average score of 5.5 and above, the focus was on non-represented countries, with an emphasis on female applicants and the thematic area of interest. A total of 5 more applications were identiﬁed, giving a total of 45 applicants accepted through the process. Other Conference Participants Considering the signiﬁcance of the conference, several stakeholders who were considered indispensable for its success received direct invitations based on their expected roles at the conference. Others were partners or collaborators in the broader Academic Freedom programme that the Council runs. These included members of the Committee reviewing the Kampala Declaration. This committee was an automatic part of the conference attendance. An additional 39 reviewers were approached to review the 173 full papers submit- ted in response to the call. Most of them were invited because of their expertise in the theme of this conference and will play a signiﬁcant role in anchoring several elements of the organisation and running the meeting. On average, each of these reviewers read 9 full papers. Furthermore, the Council extend- ed invitations to several regional and international bodies working on di^erent aspects of higher education and academic freedom. They included the Association of African Universities (AAU), the African Research Universities Association (ARUA), the United Nations Educational, Scientiﬁc and Cultural Organisation (UNESCO), the West African Higher Education Network for Excellence known by its French acronym (REESAO), Scholars at Risk, the African and Malagasy Centre for Higher Education (CAMES), and the African Studies Association of Africa. Some of these partners agreed to attend the conference. Finally, CODESRIA partners and funders were also invited, while some civil society groups were invited to share their perspectives on intellectual freedom. Selected Papers by Theme An analysis of the accepted papers highlights key themes related to academic freedom that are of immense interest to the applicants. Higher education management and governance, along with gender diversity, attracted the most submissions. These were followed by university associational life (sta^ and students). Additionally, the strong inﬂuence of neoliberal forces on higher education was reﬂected in a high number of papers on this topic. Table 2 presents the thematic breakdown. Table 2: (View PDF File) Final Selected Papers by Region/Country By geographical region, East Africa, West Africa and southern Africa had the highest number of papers accepted (14). North Africa had the lowest representation by number of papers (3), while Central Africa and papers by authors from outside Africa had 5 papers each. In West Africa, Nigeria had 6 papers accepted, while Ghana, Côte d’Ivoire, Senegal and Cape Verde each had 2 papers selected. Of the successful papers from southern Africa, South Africa contributed 7 papers, Zimbabwe 4, Eswatini 2 and Namibia 1. The 14 selected papers from East Africa came from Kenya (5), Uganda (4) and Tanzania (3), with Eritrea and Ethiopia completing the count with one paper. Central Africa had 5 papers, represented by Cameroon (4) and 1 paper from the DRC. Algeria, Egypt and Tunisia each made one contribution from North Africa. Five papers were accepted from scholars residing outside the continent. Accepted papers from outside the continent comprised 42% of the total, while Central Africa had the lowest acceptance rate at 12% (5 out of 41 submissions). This pattern reﬂects longstanding research capacity challenges in Africa, particularly sub-Saharan Africa, emphasising the need for stronger support. Developing sustainable capacity- building programmes remains a key priority for CODESRIA. Figure 4: (View PDF File) By gender, a pattern of male dominance persists, making up 65% of all applicants, while females constituted the remaining 35%. This trend has been observed on many occasions, not only in CODESRIA activities but also in other higher education statistics on the continent, where female representation lags. However, CODESRIA continues working with its partners to address this gender discrepancy Reﬂections on the Peer Review and Selection Process Of the 173 applications reviewed, only 81 met the acceptance thresh- old (score of 6+), resulting in a 47% success rate, which is below average. Similar trends have been observed in other evaluations. For instance, the 2024 Carnegie Corporation of New York (CCNY)- funded Advanced Senior Research Grant for Higher Education received 247 proposals, with only 115 (46%) accepted. The 2023 CODESRIA College of Mentors programme had a 36% acceptance rate (45 out of 124), falling short of its goal of funding 50 students. The CODESRIA 2023–2024 Meaning-Making Research Initiative review highlighted concerns over weak proposals from African academics, particularly in Lusophone and Francophone regions, and emphasised the need for methodological training to improve submissions. It is for this reason that the Council has proposed, within the frame- work of its partnership with CCNY, to commence a series of methodology training workshops to address this gap and others related to it. Conclusion This conference aims to foster ongoing scholarly and policy engagement on academic freedom in Africa. The academic community, especially African scholars, has responded positively. Bringing together experts to address challenges and rea^irm the Kampala Declaration as a key framework is essential. Four main observations on academia and academic freedom emerge from the report. First, the large number of applications suggests that academic freedom continues to be a signiﬁcant research and advocacy issue facing African academics and intellectuals. This indicates the need for more diverse opportunities for funding and advocacy linked to issues of academic and intellectual freedom. Furthermore, the signiﬁcantly low number of papers from the civil society and non-academic community suggests the need to expand the discourse. Second, the quality of applications or proposals from African scholars remains below the expected standards set by the Secretariat. Of course, the low acceptance rate of papers does not help matters. This issue demands continuous and sustained capacity-development initiatives from CODESRIA and other partner institutions in training and (re)skilling African scholars and researchers. Third, funding to support all deserving or promising African scholars remains constrained. This calls for increased funding for higher education on the continent. Public and private institutions can help by providing more support for higher education and related training. Lastly, there is a need for more creative ways to support fe- male colleagues in academia. The proportion of applications and, consequently, selected candidates continues to be largely male-dominated. While CODESRIA has instituted policies and interventions to support female admission to various programmes and activities, this report sup- ports earlier observations that the higher education fraternity in Africa needs more targeted and sustained initiatives to support greater female representation in academia.